Does the End Justify the Means? An Analysis of Outcomes in Recipients of Combined Kidney/Hematopoietic Stem Cell (HSC) Transplants and Comparison to Standard of Care (SOC) Patients. (July 2018) - Ildstad, Suzanne; Leventhal, Joseph; Shetty, A; Gallon, Lorenzo; Stare, Dianne
Abstract : Eliminating the long term costs and side effects of immunosuppression (IS) is a compelling reason to pursue transplant tolerance. Tolerance in kidney transplant (KTx) pts has been achieved through the infusion of donor HSC under some form of conditioning. The increased upfront cost and intensive treatment required by tolerance protocols demands that long term outcomes be superior to that achieved with SOC IS regimens. Since 2009 we have conducted a Phase 2 trial of combined HSC/living donor KTx in mismatched and unrelated pts where the goal has been establishment of durable donor macrochimerism. Our protocol is based upon tolerogenic CD8+/TCR-facilitating cells (FCRx). Recipients were conditioned with fludarabine (30mg/m2 days -5, -4, -3), cyclophosphamide (50mg/kg day-3 and+3), 200 cGy TBI (day-1) followed by KTx (day0). A G-CSF mobilized donor leukopheresis product was performed >2 weeks pre-KTx, processed to remove graft-versus-host disease (GVHD)-producing cells yet retain CD34 + cells and FC, and cryopreserved until use day+1 post-KTx. TAC + MMF based IS was weaned and discontinued at 1 year if chimerism, normal renal fcn and normal KTx biopsy were noted. The 1st 20 FCRx subjects with > 5 years of follow up were compared to a cohort of SOC pts from 2009-2012 who would have been eligible for our Phase 2 trial(n=166). SOC KTx received Alemtuzumab induction and TAC + MMF IS w.o oral steroids. 34 SOC underwent planned CNI conversion and were excluded from analysis. In the remaining 132 SOC there were 13 graft losses and 9 deaths with resultant overall patient survival (PS) of 93.2 % and graft survival (GS) of 83.3%. In the FCRx cohort there were 2 graft losses and 1 death, with PS of 95% and GS of 85%. Current mean eGFR (CKD-EPI) for tolerant (tol) FCRx with durable chimerism off all IS (n=11, 75.8ml/min/1.73m2) was superior to that of transiently chimeric FCRx (n=6, 62.3 ml/min/1.73m2) or SOC (53.1 ml/min/1.73m2, p = 0.0017, tol vs SOC ). Med Rx for hypertension and hyperlipidemia was common in SOC KTx(82.8% and 43%) but uncommon in tol FCRx (18% and 9%). In summary PS and GS at five yrs was comparable between FCRx and SOC. Tol FCRx had significantly better renal function than SOC. Med Rx for hypertension and hyperlipidemia was more common in SOC than tol FCRx. We conclude there are significant long term medical benefits to establishing tolerance in KTx using the FCRx approach.